Literature Review : Implementasi Peran Konseling Kepolisian dalam Pembinaan Anggota Kepolisian - Sri Utami; Dewi Sulastri; Fathonah Fitri Utami; Syindi Jumaliza; Muhammad Farhan Afandes; Affan Yusra (CV. Multi Kreasi Media, 2022)
One of the programs in the police development process that can be done by counselors is to provide counseling services. This article study aims to find out how the role of counseling is in fostering members of the police force and to find out how the influence of police counseling on members of the police force. By using a literature review or